An environmental impact assessment data information management system for geological disposal of high-level waste - CHEN HAILONG; ZHAO YANGJUN; LIAN BING; LI YANG; YANG JIE (2019)
An environmental impact assessment data information management system for geological disposal of high-level waste is disclosed, including a data server, specifically including: a customer applicationunit, and a data service unit, the following modules are set in the data service unit: a communication processing module, basic data processing module, subject data processing module and data exchangedevice which are connected with the communication processing module of the server, and adopt wired and wireless mode to realize the data exchange between the server and the client. The client is usedfor remotely inputting data to the data server, remotely querying data from the data server, and remotely sending management instructions to the data server. Based on the repository safety assessmentrequirements, the system synthesizes the data processing, analysis and calculation, and has the ability to extract the relevant parameters required by assessment from a large number of data. The datasecurity is higher, and the